2019
DOI: 10.1016/j.cois.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics and transcriptomics of host–pathogen interactions in insects: evolutionary insights and future directions

Abstract: Classical evolutionary studies of protein-coding genes have established that genes in the canonical immune system are often among the most rapidly evolving within and between species. As more genomes and transcriptomes across insects are sequenced, it is becoming clear that duplications and losses of immune genes are also a likely consequence of hostpathogen interactions. Furthermore, particular species respond to diverse pathogenic challenges with a wide range of challenge-specific responses that are still po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 92 publications
0
27
0
Order By: Relevance
“…However, we find support for an alternative hypothesis that suggests AMP diversity may be due to highly specific interactions between AMPs and subsets of pathogens that they target. Burgeoning support for this idea also comes from recent evolutionary studies that show Drosophila and vertebrate AMPs experience positive selection (Unckless et al, 2015; Unckless and Lazzaro, 2016; Hanson et al, 2016; Chapman et al, 2018; Hellgren and Sheldon, 2011; Tennessen and Blouin, 2008; Sackton, 2019), a hallmark of host-pathogen evolutionary conflict. Our functional demonstrations of AMP-pathogen specificity, using naturally relevant pathogens (Juneja and Lazzaro, 2009; Cox and Gilmore, 2007), suggest that such specificity is fairly common, and that certain AMPs can act as the arbiters of life or death upon infection by certain pathogens.…”
Section: Discussionmentioning
confidence: 98%
“…However, we find support for an alternative hypothesis that suggests AMP diversity may be due to highly specific interactions between AMPs and subsets of pathogens that they target. Burgeoning support for this idea also comes from recent evolutionary studies that show Drosophila and vertebrate AMPs experience positive selection (Unckless et al, 2015; Unckless and Lazzaro, 2016; Hanson et al, 2016; Chapman et al, 2018; Hellgren and Sheldon, 2011; Tennessen and Blouin, 2008; Sackton, 2019), a hallmark of host-pathogen evolutionary conflict. Our functional demonstrations of AMP-pathogen specificity, using naturally relevant pathogens (Juneja and Lazzaro, 2009; Cox and Gilmore, 2007), suggest that such specificity is fairly common, and that certain AMPs can act as the arbiters of life or death upon infection by certain pathogens.…”
Section: Discussionmentioning
confidence: 98%
“…As AMP dysregulation can affect health, copy number variation may impose a significant challenge for the maintenance of optimal gene expression (29). Yet perhaps the most overt patterns in AMP evolution are duplication events affecting copy number, which is widespread in both humans and fruit flies (3034). Therefore, conflict between maintenance of healthy expression levels and improved immune competence may drive patterns of AMP gain/loss or changes in expression patterns.…”
Section: Introductionmentioning
confidence: 99%
“…This could be explained by different recording periods (from 5 to 24 h) used in different studies which may have influenced the results as shown in (Sandanayaka et al 2017), and other factors like the age of the plant and the type of leaf (Luo et al 2015a, b;Ebert et al 2018), the pathogen titre in the plant or the insect, pathogen genotype and insect age. The molecular interactions that mediate feeding changes are not fully characterized or known for many pathosystems but, with the advent of functional genomics more pathways are being discovered that point out the important role that pathogen related proteins have on the vectors' phenotypic changes (Tamborindeguy et al 2017;Sackton 2018;Mauck et al 2019;Sugio et al 2015;Bernardo and Singer 2017). In absence of 'omics' data and based on other pathosystems, we propose that the feeding effects observed in our study could be due to the result of bacteria-vector specific responses, pointing out to a possible manipulation by the pathogen.…”
Section: Probing Behaviour Of Clso-infected and Non-infected B Cockementioning
confidence: 99%
“…This hypothesis depends on two conditions being met which are that the vector's altered behaviour benefits the pathogen and that the altered behaviour is controlled by the pathogen (Mauck et al 2019;Bernardo and Singer 2017). The molecular pathways by which pathogens induce phenotypic changes in the vectors are not fully understood or known for all pathosystems, but work on bacteria and viruses is suggesting that pathogen specific proteins can alter vector and host plant cell morphology, signalling pathways, immune response and cell physiology (Tamborindeguy et al 2017;Sackton 2018;Mauck et al 2019;Sugio et al 2015;Bernardo and Singer 2017). The rise of functional genomic and phenomic technologies has allowed this field of research to expand rapidly in recent times, given their potential for characterizing molecules which are present in the vector (or the host plant) at any point in time of the infection cycle.…”
Section: Introductionmentioning
confidence: 99%